Genotypic and epidemiological characterization of Methicillin resistant Staphylococcus aureus (MRSA) and Coagulase Negative Staphylococcal (CoNS) strains isolated at Tygerberg Hospital - Van Zyl, Kristien Nel (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScMedSc)--Stellenbosch University, 2016.